Research Trends in Systemic Functional Linguistics Studies of Language Textbooks (2020–2025) - Istiqomah, Salma Nur; Abdurrahman, Maman (Study Program of Arabic Language Teaching, 2025)
This study aims to identify research directions, thematic patterns, and research gaps through a Systematic Literature Review (SLR). The PRISMA 2020 framework was employed to screen 445 publications, including those indexed in Scopus and in national journals indexed in SINTA 1–3. The data collection technique used in this study was documentary research, involving the systematic retrieval of scholarly articles from the Publish or Perish (PoP) database, which is indexed in Scopus and SINTA 1–3. Data analysis followed the PRISMA 2020 guidelines, which guided the identification, screening, eligibility, and inclusion processes, and ensured transparent and standardised reporting of the systematic review. The findings reveal that SFL-based studies of language textbooks during 2020–2025 are predominantly focused on ideational meaning, particularly transitivity analysis, which is widely used to examine representations of gender, ideology, and social values in English language textbooks. The second dominant strand involves interpersonal meaning, especially appraisal system analysis, while the third focuses on textual meaning through thematic structure, cohesion, and text readability. In addition, the integration of genre analysis and multimodality has emerged, indicating an expansion of SFL applications within discourse-based literacy contexts. The findings also highlight significant research gaps, including the dominance of English-language contexts, the limited number of studies on Arabic and non-Western-language textbooks, and the lack of integration among SFL, corpus-based approaches, and AI-driven analytical technologies. This study concludes that SFL research is moving toward a more integrative and multimodal paradigm, while also offering substantial opportunities to expand SFL-based studies of Arabic language textbooks to strengthen the global representation of Systemic Functional Linguistics in language education.